Vegetation structure and composition of mangrove Palo Seco Quepos, Costa Rica - Alfaro-Sibaja, Laura (2015)
The Palo Seco mangrove in the Pacific coast of Costa Rica is in a tropical wet forest-perhumid forest transition. The nearby human population and tourism are threatening its borders. We studied mangrove’s structure, composition and regeneration as a base for future comparisons. We sampled eight 10m x 10m plots. Within them, 1m2 and 16 m2 plots were established to measure seedlings and saplings. We measured 153 trees in an 800 m2 area, with an average density of 0,19 ± 0,12 Ind/m2. Avicennia germinans was the dominant species, and Avicennia bicolor the less abundant. While seed- ling’s basal area and density were high, we found a low sapling density. We found a strong positive correlation between seedling density and trees richness and density, whereas that a strong significant negative correlation between the seedling regeneration index and tree stem height, diameter and basal area. We found a positive correlation be- tween the seedling regeneration index and mangrove tree’s richness and density. We conclude that several variables have an influence in the seedling’s establishment, survival and growth, intervening in the mangrove’s maintenance and regeneration. Strong competition with other vegetation can be a major factor in sapling growth. Palo Seco mangrove has a great potential for regeneration, and stem height and diameter evidence of an old-growth ecosystem.